Daily cumulative hip moment is associated with radiographic progression of secondary hip osteoarthritis. Issue 8 (August 2017) - Tateuchi, H.; Koyama, Y.; Akiyama, H.; Goto, K.; So, K.; Kuroda, Y.; Ichihashi, N.
Summary: Objective: To investigate whether higher daily cumulative hip moment at baseline is associated with subsequent radiographic progression of hip osteoarthritis (OA) over 12 months. Design: Fifty patients with secondary hip OA, excluding patients with end-stage hip OA, participated in this prospective cohort study. Joint space width (JSW) of the hip was measured at baseline and 12 months later. With radiographic progression of hip OA (>0.5 mm/year in JSW) as dependent variable (yes/no), univariable and multivariable logistic regression analyses were performed to assess the association between load-related parameters during gait (i.e., peak hip moment, hip moment impulse, and daily cumulative hip moment [product of hip moment impulse and mean steps/day]) and hip OA progression with and without adjustment for age, body weight, and minimum JSW. Results: Of the 50 patients (47.4 ± 10.7 years old), 21 (42.0%) were classified into the progression group. The higher daily cumulative hip moment in the frontal plane at baseline was statistically significantly associated with radiographic progression of hip OA (adjusted odds ratio (OR) [95% confidence interval (CI)], 1.34 [1.06–1.70]; P = 0.013). The higher daily cumulative hip moment in the sagittal plane was also approaching significance in its association with hip OA progression (adjusted OR, 1.80 [0.99–3.26]; P = 0.052). Conclusions: In the female patients with secondary hip OA, higher daily cumulative hip moment, particularly in the frontal plane, was a predictor of radiographic progression of hip OA over 12 months. Reduction in daily cumulative hip moment by modification in gait and physical activity may potentially slow hip OA progression.